Finding a greener, cost-effective and colour-based partial or complete replacement to White Portland Cement for cast stone production using TOPSIS - Mudgal, Devanshu; Pagone, Emanuele; Salonitis, Konstantinos (Springer, 2024)
As per recent research, the use of White Portland Cement (WPC) in the production of cast stone results in significant carbon emissions. This study aims to identify alternatives to WPC that have lower carbon emissions and are cost-effective. A literature review was performed, and data were gathered on WPC and its alternatives. Based on the literature review, five alternatives were identified. An investigation was conducted to determine the most suitable replacement for WPC based on four criteria. Automatically weighted TOPSIS which is a Multi-Criteria Decision Analysis (MCDA) was used to identify the optimal substitute for WPC. The results of the analysis were used to make a final recommendation. Overall, this study provides valuable insights into the potential substitutes for WPC in the production of cast stone, which could help to reduce carbon emissions and promote greater sustainability in the construction industry.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; 12 Responsible Consumption and Production; White Portland Cement; Multi-Criteria Decision Analysis; Cast stone; Alternative